The effect of APF-incorporated phosphoric acid etchant on shear bond strength of orthodontic brackets - Behnam Khosravanifard; Reyhaneh Yazdani; Hamid Rakhshan; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2011)
Background: The aim of this study was to evaluate the effect of adding acidulated phosphate fluoride (APF) to phosphoric acid etchant on shear bond strength (SBS) and adhesive remnant index (ARI) of orthodontic brackets bonded to etched teeth. Methods: In this in vitro experimental study, 40 human premolars were etched with 37% phosphoric acid solution (Dentsply) blended with 0, 25%, 50%, and 75% fractions of 1.23% APF (Dentsply). The brackets (Mini Dyna Lock, 3M) were bonded (Transbond XT, 3M) and were subjected to 96 hours of 37°C incubation and thermocycling procedures (2000 cycles, 5-55°C, dwell time = 30 s). Then, they were debonded at 1-mm crosshead speed to measure the SBS. The ARI was estimated at 10× magnification. The data were analyzed using the tests one-way analysis of variance (ANOVA), Tukey, chi-square, one-sample t-test, and Spearman correlation. Results: The SBS of the groups control, 25%, 50%, and 75% APF were 11.90±2.72, 8.01±3.13, 5.40±2.51, and 3.27±2.01 MPa, respectively. Mean ARI scores of these groups were 2.4 (control), 4.3, 4.7, and 4.8, respectively. According to the Tukey's test, only the mean SBS of the second group (25%) was not different from the control group (P=0.091). Conclusion: Adding about 20-25% of 1.23% APF to the phosphoric acid etchant might considerably reduce the amount of residual adhesive, without compromising the SBS.